2015
DOI: 10.1016/j.jmb.2015.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Acidic Residues in the Hfq Chaperone Increase the Selectivity of sRNA Binding and Annealing

Abstract: Hfq facilitates gene regulation by small non-coding RNAs (sRNAs), thereby affecting bacterial attributes such as biofilm formation and virulence. E. coli Hfq recognizes specific U-rich and AAN motifs in sRNAs and target mRNAs, after which an arginine patch on the rim promotes base pairing between their complementary sequences. In the cell, Hfq must discriminate between many similar RNAs. Here, we report that acidic amino acids lining the sRNA binding channel between the inner pore and rim of the Hfq hexamer co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 41 publications
1
22
0
1
Order By: Relevance
“…2b, c). As previously observed (19), the rate of RNA annealing increased with added E. coli Hfq, reaching a maximum value in 50 nM Hfq 6 , which equals the amount of molecular beacon. For target-U6 RNA, annealing was 15 times faster with 50 nM Hfq, compared to the no Hfq background (0.08 s −1 to 1.3 s −1 ; Fig.…”
Section: Rna Annealing Activity Of Hfq From Different Bacteriasupporting
confidence: 86%
See 1 more Smart Citation
“…2b, c). As previously observed (19), the rate of RNA annealing increased with added E. coli Hfq, reaching a maximum value in 50 nM Hfq 6 , which equals the amount of molecular beacon. For target-U6 RNA, annealing was 15 times faster with 50 nM Hfq, compared to the no Hfq background (0.08 s −1 to 1.3 s −1 ; Fig.…”
Section: Rna Annealing Activity Of Hfq From Different Bacteriasupporting
confidence: 86%
“…Importantly, complementary sequences in the sRNA and mRNA target also interact with an arginine patch (R16, R17 and R19) on the rim of the E. coli Hfq hexamer (13, 14, 15, 16, 17) that is essential for Hfq’s RNA annealing activity (15). In vitro annealing assays showed that E. coli Hfq accelerates sRNA-mRNA base pairing 30 to 100 times by nucleating the double helix between two complementary RNA strands (18, 19). This annealing activity is eliminated when all three arginines are replaced with alanine, and even an arginine to lysine substitution reduces E. coli Hfq’s chaperone activity (15).…”
mentioning
confidence: 99%
“…Although fulllength Hfq102 prioritizes Class II sRNAs, Hfq65 binds most sRNAs equally. Because Hfq is limiting in the cell (46), this redistribution of Hfq could disrupt sRNA-mRNA regulatory networks or affect the accumulation of sRNAs when the CTD is absent (31).…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, a study that examined sRNA accumulation and target mRNA regulation in E. coli strains expressing various Hfq mutants from the chromosome [16], showed that while mutations in some conserved proximal face residues (such as Q8, F42 and K56) affected most sRNAs analyzed, mutations in other proximal face residues (such as D9 and F39) had varying effects toward different sRNAs. It also was recently reported that certain acidic residues (D9, E18 and E37) on the proximal face of the E. coli protein are important for the discrimination of sRNAs from other cellular RNAs; mutations of these residues allowed for more non-discriminant Hfq binding to RNA while reducing the efficiency of the sRNA-mRNA annealing [17]. Generally, although sRNAs appear to be similarly anchored to the proximal face of Hfq via the polyU tail of the Rho-independent terminator, there are some differences in the way individual sRNAs contact this face.…”
Section: Binding Of Srnas and Mrnasmentioning
confidence: 99%